The Role of IL-22 in Viral Infections: Paradigms and Paradoxes - Gimeno Brias, Silvia; Stack, Gabrielle; Stacey, Maria A.; Redwood, Alec J.; Humphreys, Ian R. (Frontiers in Immunology, 2016)
Interleukin-22 (IL-22) is a member of the IL-10 family of cytokines. Hematopoietic cells express IL-22, and this cytokine signals through the heterodimeric IL-22R expressed by non-hematopoietic cells. A growing body of evidence points towards a role for IL-22 in a diverse array of biological functions ranging from cellular proliferation, tissue protection and regeneration, and inflammation. In recent years, the role that IL-22 plays in antiviral immune responses has been examined in a number of infection models. Herein, we assess our current understanding of how IL-22 determines the outcome of viral infections and define common mechanisms that are evident from, sometimes paradoxical, findings derived from these studies. Finally, we discuss the potential therapeutic utility of IL-22 manipulation in the treatment and prevention of viral infections and associated pathologies.